2013
DOI: 10.1007/s10396-013-0488-6
|View full text |Cite
|
Sign up to set email alerts
|

Pimobendan improves right ventricular myocardial contraction and attenuates pulmonary arterial hypertension in rats with monocrotaline-induced pulmonary arterial hypertension

Abstract: Both a reduction in RVSP and improvement in myocardial contraction were demonstrated with administration of pimobendan in rats with PH induced by MCT. Echocardiography evaluation of systolic function seems to be useful for monitoring excess administration of pimobendan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“… 19 , 54 , 55 However, our previous study in rats with MCT-induced PAH (30 mg/kg of MCT subcutaneously) did not find differences between rats given 6 weeks of pimobendan at 1.25 mg per rat and those in the model group; these results may differ from those of the present results due to the different disease stage induced by the lower dose of MCT and higher dose of pimobendan administered. 56 Administration of PDE-3 inhibitors for prolonged periods is related to development of myocardial hypertrophy. 57 59 Although only a fixed dose was used in our investigation, a larger study is necessary to demonstrate the lowest effective dose, as has been suggested by successful individual treatments with single or combined administrations of pimobendan at lower than recommended doses.…”
Section: Discussionmentioning
confidence: 99%
“… 19 , 54 , 55 However, our previous study in rats with MCT-induced PAH (30 mg/kg of MCT subcutaneously) did not find differences between rats given 6 weeks of pimobendan at 1.25 mg per rat and those in the model group; these results may differ from those of the present results due to the different disease stage induced by the lower dose of MCT and higher dose of pimobendan administered. 56 Administration of PDE-3 inhibitors for prolonged periods is related to development of myocardial hypertrophy. 57 59 Although only a fixed dose was used in our investigation, a larger study is necessary to demonstrate the lowest effective dose, as has been suggested by successful individual treatments with single or combined administrations of pimobendan at lower than recommended doses.…”
Section: Discussionmentioning
confidence: 99%
“…Several characteristics of maladaptive RV remodeling in the PAH model have been proposed, including RV dilation, reduced function, fibrosis, and capillary rarefication ( 29 , 150 ). However, as of the confounding effects of potentially altered pulmonary vascular resistance, hypoxia, molecular modulation (e.g., VEGF inhibition), or toxins on RV function, the MCT and SuHx models cannot be used to investigate isolated RV effects of potential therapies, and the PAB model is relevant in this regard ( 29 , 151 , 152 ).…”
Section: Surgical Modelsmentioning
confidence: 99%
“…28 In rats with pulmonary arterial hypertension, pimobendan resulted in improved echocardiographic parameters of systolic function. 29 Healthy horses that received pimobendan IV had echocardiographic changes that indicated positive inotropic effects. 30 Empiric recommended dosing in rabbits is 0.1 to 0.3 mg/kg orally every 12 to 24 hours.…”
Section: Pharmacokinetics Of Pimobendan Following Oral Administration...mentioning
confidence: 99%